2022
DOI: 10.3390/nu14040738
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Adherence to the Mediterranean Diet in Spanish Children and Adolescents: The PASOS Study

Abstract: A progressive shift away from traditional healthy dietary patterns, such as the Mediterranean diet (MedDiet), has been observed in recent decades. The aim of this study was to assess determinants of optimal adherence to the MedDiet in Spanish children and adolescents. A cross-sectional analysis was included in the PASOS nationwide representative study in Spain. Participants were 3607 children and adolescents; 8–16 years old. Primary and secondary outcome measures of weight and height were measured. Adherence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 44 publications
(60 reference statements)
6
8
0
2
Order By: Relevance
“…However, the results showed that both ODM and ODF had a better level of physical activity and psychological state than PDM and PDF, respectively, with the differences being significant in competence in the case of females and relatedness in the case of males. Regarding the level of physical activity, the results were similar to those from previous research, in which adolescents with a higher AMD showed a higher level of physical activity [ 80 ]. This could be because one of the main determinants for adopting other healthy lifestyle habits during adolescence is the practice of physical activity [ 81 ].…”
Section: Discussionsupporting
confidence: 88%
“…However, the results showed that both ODM and ODF had a better level of physical activity and psychological state than PDM and PDF, respectively, with the differences being significant in competence in the case of females and relatedness in the case of males. Regarding the level of physical activity, the results were similar to those from previous research, in which adolescents with a higher AMD showed a higher level of physical activity [ 80 ]. This could be because one of the main determinants for adopting other healthy lifestyle habits during adolescence is the practice of physical activity [ 81 ].…”
Section: Discussionsupporting
confidence: 88%
“…Selanjutnya dilakukan analisis risiko PTM berdasarkan varibel yang telah diukur. Adapun tingkat risiko PTM dilihat dari kombinasi antara indeks massa tubuh (IMT) dan rasio lingkar pinggang terhadap tinggi badan atau waist-height ratio (WHtR) (Bibiloni et al, 2022) Tabel 3 menunjukkan dengan jelas bahwa setelah dilakukan analisis lebih lanjut, ternyata hampir 40% mahasiswa memiliki risiko yang tinggi untuk menderita PTM, dengan 10% diantaranya bahkan memiliki risiko yang sangat tinggi. Hal ini sangat mengkhawatirkan terutama jika mengingat bahwa mahasiswa adalah masa depan daerah ini dan mahasiswa juga merupakan kelompok yang berpotensi untuk terabaikan sebagai target penerima layanan program Kesehatan.…”
Section: Metodeunclassified
“…Hasil penelitian sebelumnya menyebutkan bahwa remaja yang masuk dalam kategori berisiko tinggi dan sangat tinggi berdasarkan indikator gabungan antara IMT dan rasio lingkar pinggang terhadap tinggi badan (WHtR) memiliki karakteristik yang mendukung munculnya PTM. Karakteristik tersebut antara lain tingkat aktivitas yang tidak sesuai anjuran, menggunakan gadget lebih dari 2 jam per hari, memiliki pola makan yang tidak sehat, serta memiliki skor perilaku obesogenic yang tinggi (Bibiloni et al, 2022). Di Indonesia sendiri, factor risiko PTM pada remaja adalah tingkat aktivitas fisik yang tidak sesuai anjuran, konsumsi sayur dan buah yang rendah, konsumsi minuman ringan dan makanan cepat saji yang tinggi (Rachmi et al, 2020;Rosdewi et al, 2020).…”
Section: Metodeunclassified
“…As consequence, most children of western populations do not achieve the dietary goals of nutritional guidelines [11,12]. Spain is not an exception [13,14]. A recent study pointed out that ultra-processed foods have replaced fresh foods in the dietary pattern of Spanish children in last years [13].…”
Section: Introductionmentioning
confidence: 99%